Marginal fault systems of the Northern Carnarvon Basin: Evidence for multiple Palaeozoic extension events, North-West Shelf, Australia - I'Anson, A.; Elders, Chris; McHarg, S. (Elsevier, 2019)
Palaeozoic structures along the North-West margin of Australia have long been recognised as fundamental events responsible for the formation of the offshore basins that comprise this prolific hydrocarbon producing region. However, the tectonic setting in which this rifting occurred remains unclear. Detailed mapping of the geometry and tectono-stratigraphy of Permian and Carboniferous structures of the inboard Barrow, Dampier and Beagle sub-basins of the Northern Carnarvon Basin is possible using regional scale interpretation of publicly available 2D and 3D seismic data. Through seismic interpretation and mapping, we show two distinct orientations of structures that provide evidence for a poly-phase rift history of the North-West margin during the Palaeozoic. NNE trending faults of the Candace Terrace (Barrow sub-basin) were initiated in the Carboniferous or Devonian but were underfilled, resulting in erosion of the fault block crest and filling of the remnant rift-related topography by conformable sequences of later Permian and Triassic sediments. By contrast, NE-SW oriented faults of the Mermaid Nose (Dampier sub-basin) experienced a distinct phase of Permian activity and are unconformably overlain by Triassic sediments. In the Beagle sub-basin, both orientations of structures are present. Throughout the marginal fault systems of the Northern Carnarvon Basin, complex fault geometries and significant deformation of hanging wall strata are associated with reactivation of the eroded fault block crests and overprinting of faults during subsequent Mesozoic extension. This has implications for understanding the geodynamic evolution of a poly-phase extensional continental margin.